2015
DOI: 10.1007/s12687-015-0212-x
|View full text |Cite
|
Sign up to set email alerts
|

“Awakening to” a new meaning of being at-risk for arrhythmogenic right ventricular cardiomyopathy: a grounded theory study

Abstract: Efforts of social scientists to understand how individuals living in a family at risk for a genetically linked condition make health care decisions, having brought to the forefront the contextual nature of risk perception. Using a grounded theory approach, this study examines the experiences of 29 individuals living in families at risk for arrhythmogenic right ventricular cardiomyopathy (ARVC). Attention is paid to how individuals (re)construct the meaning of being at risk in relation to the developing science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…This article reports on one aspect of a qualitative study that examined the experiences of 29 individuals living in families at risk of ARVC/D (Manuel, 2013). A grounded theory (Glaser & Strauss, 1967) approach guided that research study, as outlined in previous publications (Manuel & Brunger, 2014, 2015). In grounded theory, qualitative data are collected to gain a fuller understanding of individuals’ lived experiences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This article reports on one aspect of a qualitative study that examined the experiences of 29 individuals living in families at risk of ARVC/D (Manuel, 2013). A grounded theory (Glaser & Strauss, 1967) approach guided that research study, as outlined in previous publications (Manuel & Brunger, 2014, 2015). In grounded theory, qualitative data are collected to gain a fuller understanding of individuals’ lived experiences.…”
Section: Methodsmentioning
confidence: 99%
“…For the ARVC/D population, the ICD is life-saving; without an ICD, the first symptom of heart failure might be death. Several studies have examined the experience of living with ARVC/D in NL (Etchegary et al, 2016; Etchegary et al, 2015; Manuel & Brunger, 2014, 2015); however, findings have not specifically reported on what life is like to have an ICD. For nurses to provide care that is tailored to the needs of this population, they must have a fuller understanding of how these individuals adjust to and cope with having an ICD within the context of a genetic condition such as ARVC/D.…”
mentioning
confidence: 99%
“…12 Although the psychosocial implications for patients with ARVC have not been studied extensively, other inherited cardiomyopathies or dysrhythmia syndromes such as hypertrophic cardiomyopathy and Brugada syndrome have been more widely researched, particularly with regard to ICD-related concerns, and may be applicable across this inherited disease spectrum. 12,13 Recognizing the psychosocial effect of necessary lifestyle adjustment, including living with an ICD, is important in any clinical setting. Patients with ARVC have unique and diverse needs that may evolve at different stages of life, and ongoing assessment and sensitivity to these needs is important for clinicians in any specialty who are treating patients with ARVC.…”
Section: Psychosocial Effectsmentioning
confidence: 99%
“…Patients with ARVC have unique and diverse needs that may evolve at different stages of life, and ongoing assessment and sensitivity to these needs is important for clinicians in any specialty who are treating patients with ARVC. 13…”
Section: Psychosocial Effectsmentioning
confidence: 99%
See 1 more Smart Citation